PERANCANGAN KONVEYOR RANTAI KAPASITAS 8 TON PER JAM - Angrian Rante; Stenly Tangkuman; Michael Rembet (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
Conveyor is an auxiliary equipment in a production process. The main component of a chain conveyor is chain . This chain is driven through a sprocket which is connected to an electric motor through a reduction gear. Process of designing a chain conveyor required several parameters that are : the characteristics of the transported material, conveyors geometry, conveyors capacity and conveyor speed. Design resulted in chain dimension and the required motor power. Comparing the design to the existing conveyor as a case of study, it was found that the electric motor used is larger than necessary which in turn that the speed of the chain there can still be improved in order to increase production capacity. Keywords : Design , Chain-Belt Conveyors, Conveyor Capacity